PROSES PEMBENTUKAN DERIVASI DAN INFLEKSI PADA RUBRIK EDUKASI KOMPAS.COM - Imamul Mutaqin; Irsyadi Shalima; Herpindo Herpindo (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
The word formation process is inseparable from the morphological process of affixation. The formation of verb word classes can be derived from verb, noun, adjective, and adverb word classes. This phenomenon causes morphological symptoms of derivation and inflection. Derivation is the process of forming new words that cause changes in lexical identity, while inflection does not change lexical identity. This study aims to obtain a description of the process of forming derivation words and forming inflected words on Kompas.com. Research using qualitative methods. The data and data sources used are online news Kompas.com, the January 2022 edition of the education rubric. The analysis technique used in analyzing the data uses the distribution method with the direct element division technique. The results of this study found words that experienced derivation and inflection with various kinds of forming affixes. Derivative and inflected affixes in Kompas.com consist of prefixes, suffixes, confixes and combinations of affixes. Initial prefixes or affixes are in the form of meN-, di-, ke-, ber-, ter, se-, and peN-; suffixes or final affixes consist of -an, -i, and -kan; confix affixes have forms of ke-an, penN-an, per-an, and beran; as well as combinations of affixes consisting of the forms of memper-/-kan, meN- -i, di-/-i, meN-/-kan, di-/-kan, diper-/-kan, and diper-/-i. The phenomenon of the affix meN- is an affix that forms an active verb, while the affix di- forms a passive verb. Also found ter- and ke-an affixes which are affixes forming anti-passive ergative verbs. Based on the productivity aspect, inflection is more productive than derivation.